Perceived effectiveness of pictorial health warnings on changes in smoking behaviour in Asia: a literature review - Suci Puspita Ratih; Dewi Susanna (BMC, 2018)
Abstract Background Several Asian countries have implemented pictorial health warnings on cigarette packs as suggested by the World Health Organization with various policies based on countries' systems. The study is aimed to analyse multiple research studies on the perceived effectiveness of Pictorial Health Warnings as a deterrent to smoking intention and as a stimulant of smoking behaviour in smokers and non-smokers in Asian countries. Method Peer-reviewed articles were identified through multiple science databases indexed by Scopus, MEDLINE or PubMed. The review was limited to articles that reported original research findings, were conducted in Asian countries and were available for review by January 2010. A PRISMA Flow diagram was used to identify the articles through the process of data screening and extractions. Result A total of 14 original articles which met the criteria were included in the review, consisting of 12 quantitative studies and 2 studies with both quantitative and qualitative methods from 17 jurisdictions. The reviewed studies found that pictorial health warnings were associated with a greater perception of salience (reading and noticing the warning), emotional effects, and cognitive increase. Additionally, in the reviewed studies, pictorial health warnings were perceived as more effective in deterring smoking initiation and encouraging smoking cessation than text-only warnings. Several studies also evaluated the effectiveness of a new pictorial warning compared with the old one. However, the relevance of refreshing the pictures of pictorial health warnings and the length of the effective period of the implementation of pictorial health warnings were less frequently studied. Conclusion Pictorial health warnings perceived as more effective in deterring smoking initiation among non-smokers and as well as in stimulating smoking cessation among smokers. Future studies on pictorial health warnings should study the relevance of changing or refreshing pictorial health warning on cigarette packages in a period of time.